Perisian multimedia berasaskan animasi bagi pembelajaran subtopik isihan - Eh Phon, Danakorn Nincarean (2011)
Looking at the scenario of reformation in Malaysia education system which is growing rapidly in the era of information technology nowadays, teaching and learning problems mostly can be solved by using multimedia which is now is one of the most important technology. Therefore, the purpose of this study is to design and develop multimedia courseware that based on animation approach on the topic of Sorting Algorithms. Based on ADDIE instructional design method, this multimedia courseware was developed based on constructivisme approaches. The evaluation process was conducted to obtain students feedback towards their understanding and the main aspects of design which are information design, interaction design and presentation design of the developed courseware. The study sample for this study consisted of 20 students from Faculty of Electrical Engineering, Universiti Teknologi Malaysia who had taken Data Structure and Algorithm subject. The instruments used to gather the data were questionnaire and interview. Results based on the analysis showed that the interface design recorded a highest score of mean (mean=4.30) followed by the information design (mean=4,24) and interaction design (mean=4.20). For interview technique, the formation of themes was done based on the feedback given by the respondents and the analysis had shown that the respondents gave positive feedbacks. Based on the findings of the study, a researcher can conclude that the courseware can be used to assist in learning.